Limiting factors in acoustic density separation of carbon particles in air - Karpul, David (Department of Electrical Engineering, 2014)
Particles suspended in a fluid that is exposed to an acoustic standing wave experience a time-averaged force that drives them to either the pressure nodes or anti-nodes of the wave. Several filter designs have been successfully implemented using this force to filter small particles in liquids with low flow rates and small cross-sectional areas. It has been suggested that the filtration of small solid particles out of a gas, such as carbon in air (smoke), would be a possible application of acoustic density separation. The emissions created by the combustion of hydrocarbons used in industrial processes, electricity production and transport significantly damage human health and the world at large. Particulate matter released, primarily by power plants, is currently removed from the emissions by highly space consuming and expensive equipment. The creation of a new type of particulate filter, which is both more cost effective and less space consuming, would be beneficial to the industry and consequently the environment at large. This study shows the limiting factors, in both power requirements and design factors, of an acoustic filter designed for filtering smoke particles across large cross-sectional areas at high flow rates, as in the case of an industrial smoke stack. It is shown that while filtration is possible, the power needed is impractical. It is also shown that operating the filter above a particular threshold intensity the energy usage of the filter is optimised.